Answer:
arithmetic sequence: 24, 42, 66, 90, 114; y = 24x - 30
geometric sequence: -54, 162, -486, 1458, -4374; y = -6(-3)^(x - 1)
Step-by-step explanation:
Arithmetic sequence:
-6, 18, ...
18 - (-6) = 24
18 + 24 = 42
42 + 24 = 66
66 + 24 = 90
90 + 24 = 114
y = -6 + 24(x - 1)
y = -6 + 24x - 24
y = 24x - 30
Geometric sequence:
-6, 18, ...
18/(-6) = -3
18 * (-3) = -54
-54 * (-3) = 162
162 * (-3) = -486
-486 * (-3) = 1458
1458 * (-3) = -4374
y = -6(-3)^(x - 1)
Answer:
no because it doesnt pass the vertical line test
Step-by-step explanation:
give me brainliest pls
Just use y2-y2/x2-x1
so
1+5 (because subtracting a negative is the same as adding a positive)
4-2
6/2
or 3/1 which is the same as 3